2020
DOI: 10.1590/1809-2950/20023927042020
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de exergames e seus efeitos sobre a saúde física de pacientes com diagnóstico de câncer: uma revisão integrativa

Abstract: RESUMO Este estudo teve como objetivo a busca de registros com diferenças significativas a respeito da saúde física de pacientes com câncer ao praticarem exergames. Utilizou-se como método a Revisão Integrativa de Literatura com as palavras chaves “Fisioterapia”, “Realidade Virtual”, “Wii”, “Exergames” e “Câncer”, em português e inglês, nas bases de dados PubMed, Science Direct, Medline, Scopus, Lilacs, SciELO, PEDro, Cochrane e Periódicos Capes. Os critérios de inclusão foram: estudos que utilizassem exergame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Thus, we considered the physical abilities of various participants at each session in order to promote participants’ competence and desire to engage in doing the exergame activities based on their physical abilities, which can lead to better physical function. An additional potential reason may be related to increased enjoyment in participants when using the exergame as a tool to promote PA. Two reviews by Silva et al [ 17 ] and Tough et al [ 18 ] that examined the exergame interventions for persons with cancer globally (e.g., USA, South Korea, Japan, Germany, and Canada) found exergaming interventions to be more acceptable than standard of care, and they appear to improve balance, physical function, physical performance, PA levels, and reduced pain in persons with cancer. In comparison, our control group response indicated that only the appropriate activities and program length questions reach acceptability scores ≥4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we considered the physical abilities of various participants at each session in order to promote participants’ competence and desire to engage in doing the exergame activities based on their physical abilities, which can lead to better physical function. An additional potential reason may be related to increased enjoyment in participants when using the exergame as a tool to promote PA. Two reviews by Silva et al [ 17 ] and Tough et al [ 18 ] that examined the exergame interventions for persons with cancer globally (e.g., USA, South Korea, Japan, Germany, and Canada) found exergaming interventions to be more acceptable than standard of care, and they appear to improve balance, physical function, physical performance, PA levels, and reduced pain in persons with cancer. In comparison, our control group response indicated that only the appropriate activities and program length questions reach acceptability scores ≥4.…”
Section: Discussionmentioning
confidence: 99%
“…However, the added cancer-related symptom burden, such as fatigue, pain, and limited mobility from cancer or cancer treatment, can further impact how BC survivors perceive PA-related barriers and respond to PA interventions [ 11 , 12 , 15 , 16 ]. Previous exergame interventions primarily focused on using exergame itself to impact health, but it was not paired with behavioral coaching to enhance self-management skills to overcome PA-related barriers [ 17 , 18 ]. Thus, there is a need to pilot test PA interventions designed to provide both self-management skills to overcome PA-related barriers and enhance survivors’ motivation to engage in PA despite the experience of cancer-related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…(Bento et al, 2018), voltado para o auxílio no tratamento de sintomas depressivos e estimulação cognitiva e o "PhysioJoy" (Balista, 2013), utilizado para o tratamento de pacientes com déficit motor. Outros que contribuem para o aumento dos níveis de atividade física, como o caso de games de movimentos ou exergames, atuando no controle de peso e no combate ao sedentarismo e obesidade (Florêncio Júnior, Paiano;Costa, 2020;Silva et al, 2020). São encontrados também jogos de tabuleiro como "Jogo da Onda" (Adade;Monteiro, 2013), "Zig-Zaid" (Schall et al, 1999) e "Fome de Q?"…”
Section: Introductionunclassified